Analysis of the online reputation based on customer ratings of lodgings in tourism destinations - Manuel Rodríguez-Díaz; Rosa Rodríguez-Díaz; Tomás F. Espino-Rodríguez (Administrative Sciences, 2018)
This study analyzes customers' online social communication to rate lodgings and tourist destinations. A practical methodology is proposed to analyze the online reputation of lodgings as well as the main concepts rated by customers in their online social communication process. To this end, an empirical study was carried out by analyzing the online opinions expressed by customers on the Booking.com tourist lodging website. Based on the information available, three new variables were created and analyzed that represent clearly defined concepts in the minds of consumers. This includes "service quality," "perceived value," and "added value." This study shows that perceived value and service quality are concepts evaluated by customers that are able to differentiate between lodgings in tourist destinations. Therefore, the results show that the online social communication that takes place through this portal has the capacity to guide potential customers by differentiating between the services offered by lodging companies.
Keywords: 350; social media; online social communication; tourism destination; online reputation; lodging